Edukasi Mitigasi Kesehatan Reproduksi pada Masyarakat Desa Sibalaya Utara dan Sibalaya Selatan, Kabupaten Sigi, Sulawesi Tengah: Education on Reproductive Health Mitigation in the Community of North and South Sibalaya Villages, Sigi Regency, Central Sulawesi - Sumiaty Sumiaty; Siti Hadijah Batjo; Taqwin Taqwin; Widya Pani; Niluh Nita Silfia; Hastuti Usman; Kadar Ramadhan; Dwi Erma Kusumawati; Wery Aslinda; Metrys Ndama; I Wayan Supetran; Mohamad Fadli Dg. Patompo; Baharuddin Condeng; Junaidi Junaidi; Fajrillah Kolomboy; Zainul Zainul; Djunaedil Syukur Sulaeman; Novarianti Novarianti; Saharudin Saharudin; Ni Made Ridla Nilasanti (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The preparation of individual equipment in reproductive health mitigation during disasters is not known by the community. The people of Sibalaya Village have never received education on reproductive health mitigation kits during disasters. The purpose of community service is to prepare the community in reproductive health mitigation during disasters in Sibalaya Village, Tanambulawa Sub-district, Sigi, Central Sulawesi. The service method is health education and demonstration on reproductive health mitigation kits. The service was carried out in North and South Sibalaya Villages, Sigi Regency, Central Sulawesi, from October 19 to October 24, 2022. The target audience are pregnant women, mothers with toddlers, adolescent girls, and couples of reproductive age, with a total of 38 participants. The education media used a PowerPoint presentation with an LCD projector. Evaluation was conducted through pre and post-tests using a questionnaire. The service results showed that 100% of participants knew about the risk groups during disasters, >70% knew about the color of the kit, 92.11% knew about the contents of the kit, and 97.37% knew about the availability of transportation during referrals. The post-test was conducted by asking participants directly, and those who answered correctly were given a reproductive health mitigation kit as a prize. Two participants were able to demonstrate the use of the mitigation kit. The conclusion of the service is that there is an increase in knowledge, and participants can demonstrate the use of reproductive health mitigation kits. It is recommended to form a village reproductive health mitigation team and provide training.